AEM, Seismic and Power-lines: A hydrogeological case study in Peel, Western Australia. Issue 1 (1st December 2019) - Pethick, Andrew; Harris, Brett; Barron, Olga
Summary: Airborne time domain electromagnetic and high resolution 2D seismic data were acquired in 2018 to map structures of hydrogeological significance in the Peel region; Western Australia. Interpretation of the airborne electromagnetic (AEM) survey was complicated by the presence of major utilities including power lines. We consider methods for removing the impact of these sources of EM noise within processing prior to interpretation. Generally, we found this to be counterproductive as information was unnecessary lost. Imaging from high resolution seismic reflection data is unaffected by EM noise. We show how a strategically located high quality seismic imaging was instrumental in providing an interpretational framework that could be extended to the full AEM survey area. We provide examples of AEM interpretation for many hydrogeological features including: major faults, 3D hydrostratigraphic surfaces, geological dip, saline water interfaces and zones with potential hydraulic connection between shallow and deeper aquifer systems. This work facilitated significant revision of groundwater systems conceptualisation in the Peel region.